2009
DOI: 10.1097/chi.0b013e3181b395c0
|View full text |Cite
|
Sign up to set email alerts
|

Widespread Cortical Thinning Is a Robust Anatomical Marker for Attention-Deficit/Hyperactivity Disorder

Abstract: Objective This cross-sectional study sought to confirm the presence and regional profile of previously reported changes in laminar cortical thickness in children and adolescents with Attention Deficit / Hyperactivity Disorder (ADHD) compared to typically developing healthy subjects. Method High-resolution MR images were obtained from 22 (19 male, 3 female; mean age: 11.7 years) children and adolescents with ADHD and 22 age and sex matched healthy control subjects (mean age: 11.7 years). Brain tissue volumes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
99
2
8

Year Published

2011
2011
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 144 publications
(123 citation statements)
references
References 53 publications
14
99
2
8
Order By: Relevance
“…Using structural imaging, recent data from BEIP (McLaughlin et al, 2013) demonstrated that 8-year-old children with ADHD and histories of institutional rearing had widespread cortical thinning similar to what has been described in children with ADHD without histories of deprivation (Narr et al, 2009;Shaw et al, 2006). Specifically, investigators demonstrated that Romanian children reared in institutions had higher levels of ADHD symptoms and exhibited widespread reductions in cortical thickness across prefrontal, parietal, and temporal regions compared with never institutionalized Romanian children.…”
Section: Attention-deficit/hyperactivity Disordermentioning
confidence: 84%
“…Using structural imaging, recent data from BEIP (McLaughlin et al, 2013) demonstrated that 8-year-old children with ADHD and histories of institutional rearing had widespread cortical thinning similar to what has been described in children with ADHD without histories of deprivation (Narr et al, 2009;Shaw et al, 2006). Specifically, investigators demonstrated that Romanian children reared in institutions had higher levels of ADHD symptoms and exhibited widespread reductions in cortical thickness across prefrontal, parietal, and temporal regions compared with never institutionalized Romanian children.…”
Section: Attention-deficit/hyperactivity Disordermentioning
confidence: 84%
“…This finding is in line with those of previous clinical studies that have shown widespread cortical abnormalities. 9,10,13 An important strength of the present study is that, to our knowledge, no previous studies have assessed the role of cortical thickness and gyrification in the association between attention-deficit/hyperactivity symptoms and cognitive functioning. Studying this topic helps us to understand the underlying neurobiology and high comorbidity of attentiondeficit/hyperactivity symptoms and cognitive problems.…”
Section: J Psychiatry Neurosci 2017;42(2)mentioning
confidence: 96%
“…4,8 This shared genetic background suggests that a common neurobiology under lies ADHD and cognition. Previous neuroimaging studies in ADHD have shown a delay in brain maturation 9 and a thinner cortex 10 throughout most of the cerebrum. In population-based pediatric samples of both healthy children 11 and the population at large 12 the latter association has…”
Section: Introductionmentioning
confidence: 91%
“…It is interesting to note that children and adolescent with attentiondeficit/hyperactivity disorder (ADHD), like those with SCA, have shown significant reduction in brain volume, gray matter volume and cortical thickness [117]. ADHD which is strongly associated with NE [118] was reported to occur in 19-25% of children with SCA [119].…”
Section: Brain Maturation and Nocturnal Enuresis In Scamentioning
confidence: 99%